ANALISIS PERILAKU SEKSUAL MAHASISWA YANG TINGGAL DI RUMAH KOST “ STUDI KUANTITATIF DI KABUPATEN ACEH SINGKIL ” - Safitri, Arliza (Universitas Audi Indonesia, 2022)
Problems in teenagers specifically college students shows the increasing symptoms qualitatively and quantitatively, one of which is sexual behavior. Sexual behavior which exists in the community caught the attention of many people as behavior that produced worries and bring about negative effects, especially when this is done by college students who are considered as intellectual people who are able to have positive thinking, attitude and behavior in the eyes of the community. This research intend to know the students sexual behavior who are living in a rented rooms, covering students renting rooms in Kabupaten Aceh Singkil sexual knowledge, attitude and action. The type of research used is the analise research which is descriptive in nature with the quantitative approach. The population of the research is all students who are still attending universities living in rented rooms in the Kabupaten Aceh Singkil. The total sample is 60 people, with the sample collecting technique using purposive sampling. Data collection is done by using questionnaires as a guide to ask questions during interviews. The result of the research shows that the number of respondents who has “good” knowledge of sexual behavior consist of 48 people (80.0%), “normal” attitude of sexual behavior consist of 28 respopndents (46, 7%). Based on this research, it is suggested that serious attention should be given from the community leaders such as the Kepala Desa towards the sexual behavior of the room renting students to avoid unwanted matters from happening, and to give information and guidance to the caretakers and owners of the rooms so that they will be more attentive and give more supervision to the room renter students in the room they rent out.